Fostering social skills through sociology learning: a mixed-methods study of pre-service social studies teachers - Kahar Mashuri; Yusda Novianti; Masrizal Masrizal (Jurnal Konseling dan Pendidikan, 2026)
The development of social skills is a crucial demand in 21st-century higher education, particularly for pre-service teacher students. This study aims to examine the role of sociology learning in the development of social skills among students of the Social Studies Education Program at STKIP Al Maksum involving 15 students in the qualitative phase (in-depth interviews) and 60 students in the quantitative phase (instrument trial)." . The study employed an exploratory sequential mixed methods design, with a qualitative approach as the primary phase and a quantitative approach as a supportive phase. Qualitative data were collected through in-depth interviews, classroom observations, and document analysis, while quantitative data were obtained through a questionnaire developed based on the qualitative findings and analyzed using descriptive statistics. The findings indicate that sociology learning contributes significantly to the enhancement of students' social skills, particularly in interpersonal communication, social awareness, cooperation, and social responsibility. Social change: Previously passive students became more confident in expressing their opinions in group discussions. Conflict Reduction: A decrease in the frequency of interruptions between students when working on assignments together. Empathy: The emergence of an attitude of mutual assistance (peer tutoring) observed through in-depth observation. The results of the study showed a significant increase in social skills, as seen from the N-Gain score of 0.75 (High Category). Qualitatively, this was confirmed by an increase in the intensity of collaboration and students' conflict resolution abilities during the learning process in the classroom.